The Current State of Silicone-Based Dielectric Elastomer Transducers - Madsen, Frederikke B.; Daugaard, Anders E.; Hvilsted, Søren; Skov, Anne L. (Macromolecular rapid communications., 2016)
Silicone elastomers are promising materials for dielectric elastomer transducers (DETs) due to their superior properties such as high efficiency, reliability and fast response times. DETs consist of thin elastomer films sandwiched between compliant electrodes, and they constitute an interesting class of transducer due to their inherent lightweight and potentially large strains. For the field to progress towards industrial implementation, a leap in material development is required, specifically targeting longer lifetime and higher energy densities to provide more efficient transduction at lower driving voltages. In this review, the current state of silicone elastomers for DETs is summarised and critically discussed, including commercial elastomers, composites, polymer blends, grafted elastomers and complex network structures. For future developments in the field it is essential that all aspects of the elastomer are taken into account, namely dielectric losses, lifetime and the very often ignored polymer network integrity and stability. Silicone elastomers are favorable materials for dielectric elastomer transducers (DETs), but for the field to progress, a leap in material development is required and it is essential that all aspects of the elastomer are taken into account. Here, the current state of silicone elastomers for DETs is summarised and critically discussed.